PENDIDIKAN KARAKTER DALAM AL-QUR’AN SURAT LUQMAN AYAT 12-19 (TELAAH ATAS KITAB TAFSIR AL-AZHAR) - Yuda Abdul Gafur; Nuraini Nuraini; Ahmad Rathomi (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2015)
This article aims to explore character education in the perspective of the Qur'an through the interpretation of al-Azhar, so that understanding of character education is more varied and more comprehensive. The research approach used is library research, the data obtained from a literature review with a theoretical and philosophical approach. The results of the study found that the value of character education contained in Q.S Luqman verses 12-19 Tafsir Al-Azhar by Hamka was education for monotheism/divinity, education for worship, da'wah and moral/character education. And specifically includes education on God / Prohibition of associating partners with God, filial piety to parents, gratitude, honesty, worship education, amar ma'ruf nahi munkar (da'wah), patience, and moral / character education. Character education is carried out by naming values ​​subtly, lovingly like a parent to a child, in a way that can conquer the heart, not by violence and because Islam is a beautiful and peaceful religion.